(untitled) (Hekima Review, 2016)
The comparatively young discipline of Intercultural theology, which focuses predominantly on (Christian) contextual theologies, intercultural theological epistemology, interreligious comparative theology and theology of religions, owes its existence also to African-European relationships. African-European history is characterised by the colonialism of the 19th and 20th centuries, post-colonial developments, development aid and current debates about migration, globalisation and terrorism. The history of Christian theology in Africa can be read as a history of engagement with these challenges, with the paradigms of culture, liberation and reconstruction being crucial in the formation of theological theory. Intercultural theology is the result of this problematic history and is also a meta-discourse reflecting on these exploratory theological movements, thereby demonstrating its specialist experience and competence in contributing to constructive relationships between Africa and Europe.